2021
DOI: 10.1111/myc.13328
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in critically ill patients with coronavirus disease 2019‐associated pulmonary aspergillosis: A systematic review and meta‐analysis

Abstract: Reports of COVID‐19 associated pulmonary aspergillosis (CAPA) are rising, but the associated mortality and factors affecting it are not well‐characterised. We performed a systematic review including 20 peer‐reviewed English language studies reporting mortality in CAPA published till 18 February 2021from PubMed, Ovid SP, Web of Science, Embase and CINHAL. The pooled mortality in CAPA was 51.2% (95% CI: 43.1–61.1, I2 = 38%). The leave one out sensitivity analysis and influential case diagnostics revealed one out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 63 publications
2
43
2
1
Order By: Relevance
“…Recent systematic reviews and a meta-analysis of CAPA reported an overall mortality rate of 51.2% [28], 52.2% [7] and 54.9% [36]. The prospective studies of Bartoletti et al and White et al reported the mortality rates of 44% vs. 19% [24] and 58% vs. 31% [25] 30 days after ICU admission, in the CAPA group compared to the non-CAPA control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent systematic reviews and a meta-analysis of CAPA reported an overall mortality rate of 51.2% [28], 52.2% [7] and 54.9% [36]. The prospective studies of Bartoletti et al and White et al reported the mortality rates of 44% vs. 19% [24] and 58% vs. 31% [25] 30 days after ICU admission, in the CAPA group compared to the non-CAPA control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in their recent meta-analysis, Singh et al reported an overall mortality rate in CAPA patients of 52.2% [28]. However, unlike Pasquier et al, their meta-regression analysis did not reveal any association between mortality in CAPA and any risk factor, COVID-19specific therapy or anti-fungal therapy [28].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies have observed higher serum procalcitonin levels in recipients with co-infection as compared to those free from this complication [ 17 ▪ ]. The diagnosis of COVID-19-associated pulmonary aspergillosis (CAPA) has been only occasionally reported [ 15 , 17 ▪ , 25 , 26 ], and HSCT recipients are marginally represented in case series of CAPA [ 27 , 28 ]. There have been also an anecdotal report of an aseptic meningitis with negative reverse transcription polymerase chain reaction (RT-PCR) testing for SARS-CoV-2 in the cerebrospinal fluid after initial clinical recovery from COVID-19, suggesting a potential pathogenic role for molecular mimicry [ 29 ].…”
Section: The Clinical Spectrum Of Coronavirus Disease 2019 In the Hematopoietic Stem Cell Transplant Populationmentioning
confidence: 99%
“…Liver transplant recipients are associated with adverse outcomes after infection with coronavirus disease of 2019 (COVID-19) 1 . Use of high dose immunosuppression has also led to a rise in cases of invasive aspergillosis worldwide 2 . We describe a case highlighting the role of post-transplant immunosuppression and COVID-19 in causing reactivation of tuberculosis and invasive pulmonary aspergillosis, complicated by acquired Hemophagocytic Lymphohistiocytosis (HLH).…”
Section: Introductionmentioning
confidence: 99%